A Novel Cold-Adapted and Salt-Tolerant RNase R from Antarctic Sea-Ice Bacterium Psychrobacter sp. ANT206 - Yatong Wang; Yanhua Hou; Ping Nie; Yifan Wang; Xiulian Ren; Qifeng Wei; Quanfu Wang (Molecules, 2019)
A novel RNase R, psrnr, was cloned from the Antarctic bacterium Psychrobacter sp. ANT206 and expressed in Escherichia coli (E. coli). A bioinformatics analysis of the psrnr gene revealed that it contained an open reading frame of 2313 bp and encoded a protein (PsRNR) of 770 amino acids. Homology modeling indicated that PsRNR had reduced hydrogen bonds and salt bridges, which might be the main reason for the catalytic efficiency at low temperatures. A site directed mutation exhibited that His 667 in the active site was absolutely crucial for the enzyme catalysis. The recombinant PsRNR (rPsRNR) showed maximum activity at 30 °C and had thermal instability, suggesting that rPsRNR was a cold-adapted enzyme. Interestingly, rPsRNR displayed remarkable salt tolerance, remaining stable at 0.5–3.0 M NaCl. Furthermore, rPsRNR had a higher kcat value, contributing to its efficient catalytic activity at a low temperature. Overall, cold-adapted RNase R in this study was an excellent candidate for antimicrobial treatment.